Aprendizaje y habilidades sociales en preescolares de 5 años de Chilca – Huancayo - Aranda Sanabria, July Fiorella (2023)
The research that is presented is of an applied type of explanatory level, for this the experimental method was used, its objective was to establish which is more effective instructional learning or learning by model in the process of development of social skills in preschool children. 5 years of Chilca - Huancayo. The static comparison or group comparison design was used only afterwards. The sample consisted of 65 5-year-old preschoolers from the Chilca - Huancayo district, 41 preschoolers make up the experimental group and 24 preschoolers the control group. The technique used for data collection was the interview and direct observation, instructive learning and model learning were experienced, with alternate sessions for its development. The instrument used was a pedagogical test, constructed by the researcher. The main results show that learning by model was more effective than learning by instruction in the process of developing social skills in 5-year-old students from the Chilca district. It is concluded, among other things, that social skills can be learned through observation and imitation of the behaviors that most stand out in their social environment where the child develops